2014
DOI: 10.1090/s0002-9947-2014-05971-0
|View full text |Cite
|
Sign up to set email alerts
|

On the procongruence completion of the Teichmüller modular group

Abstract: For 2g − 2 + n > 0, the Teichmüller modular group Γ g

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(75 citation statements)
references
References 18 publications
0
75
0
Order By: Relevance
“…, s, and we denote by [γ] a cycle in H 1 (S K , Q) supported onγ and by , S K the standard symplectic bilinear form on H 1 (S K , Q). In Lemma 5.11 of [6], we showed that, when log(ρ U (τ mh 1 γ 1 · . .…”
Section: Centralizers Of Pro-c Multitwistsmentioning
confidence: 97%
See 4 more Smart Citations
“…, s, and we denote by [γ] a cycle in H 1 (S K , Q) supported onγ and by , S K the standard symplectic bilinear form on H 1 (S K , Q). In Lemma 5.11 of [6], we showed that, when log(ρ U (τ mh 1 γ 1 · . .…”
Section: Centralizers Of Pro-c Multitwistsmentioning
confidence: 97%
“…It is not difficult to show (cf. Section 4 [6]) that these orbits correspond to the possible topological types of the surface S σ, for σ a multicurve on S.…”
Section: The Complex Of Pro-c Curves On Smentioning
confidence: 98%
See 3 more Smart Citations